Preparation and stereolithography of SiC ceramic precursor with high photosensitivity and ceramic yield. Issue 9 (15th June 2020) - Chen, Jiangshan; Wang, Yuanjie; Pei, Xueliang; Bao, Chonggao; Huang, Zhengren; He, Liu; Huang, Qing
Abstract: Stereolithography of ceramic precursors is a valuable additive manufacturing technology for complex ceramic parts. In this study, a new SiC ceramic precursor—liquid hyperbranched polycarbosilane (LHBPCS) grafting acrylate group was synthesized by chlorinating some Si–H groups of LHBPCS with Cl2 followed by reacting with hydroxyethyl acrylate. The reaction processes and structures of intermediate reactant and target product were confirmed by FT-IR and 1 H NMR. According to photolithography experiment and hardness test under UV light, the synthesized LHBPCS had high photo-curing activity. Thermogravimetric analysis indicated it also possessed high ceramic yield (the ceramic yield at 1000 °C was 74.4%). After shaping with stereolithography, defect-free green bodies could be got. When heated to 1000 °C, the transparent yellow green bodies transformed into black SiC rich ceramic parts and 18.3–25.1% linear shrinkage associated with the precursor-to-ceramic conversion was observed. Because the shrinkage in the pyrolysis stage was nearly isotropic and the shrinkage was lower than other reported data, no obvious deformation or crack was found in the pyrolyzed parts.